KOMITMEN ORGANISASIONAL DAN LINGKUNGAN KERJA TERHADAP TURNOVER INTENTION (STUDI PADA PT VERITRA SENTOSA INTERNASIONAL) - Febrina Wijayanti; Gun Gunawan Rachman (Holistik Manajemen: Jurnal Manajemen, 2020)
The desire of employees to move (turnover intentions) in the service industry is an initial signal of resignation (resign) employees in the industry. This needs to be a concern for the company because of the high desire of employees to move (Turnover intentions) within a company can disrupt activities and productivity. Besides the desire of employees to move (Turnover intentions) can also create instability and uncertainty about labor conditions. Data on organizational commitment, work environment and employee turnover intentions and three research hypotheses were obtained through interviews using a questionnaire to 85 respondents of PT Veritra Sentosa Internasional employees. The data obtained were then analyzed using SEM analysis techniques. The results of testing the three research hypotheses using SEM analysis showed that the organizational commitment to turnover intention at PT Veritra Sentosa Internasional was classified as good. This means that the higher the organizational commitment, the lower the intention to leave or the intention to leave the employee. work environment influences turnover intention. This means that the lower working environment will further increase turnover intention. Turnover Intention at PT Veritra Sentosa International is still classified as very small, most employees feel the commitment of the organization is good and employees feel comfortable with the work environment. So that most of the employees to leave the company are still limited to their desires and have not reached the realization stage.